2000
DOI: 10.1063/1.873829
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of electron/electron instabilities: Electromagnetic fluctuations

Abstract: Electron/electron instabilities arise in collisionless plasmas when the electron velocity distribution consists of two distinct components with a sufficiently large relative drift speed between them. If the less dense beam component is not too tenuous and sufficiently fast, the electron/electron beam instability is excited over a relatively broad range of frequencies. This instability is often studied in the electrostatic limit, which is appropriate at ωe/|Ωe|≫1, where ωe is the electron plasma frequency and Ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…On the other hand, Dum and Nishikawa [1994] did two‐dimensional PIC simulations of the instability in a strongly magnetized plasma, and showed weak perpendicular scattering of the beam component. Later simulations [ Yin et al , 1998; Gary et al , 2000] suggested that pitch angle widths of the beam component tend to be broader with larger frequency ratio ω e /∣Ω e ∣, where ω e and Ω e are the electron plasma and cyclotron frequencies. Lately, Gary and Saito [2007] demonstrated electron beam broadening by the e/e instability in a weakly magnetized plasma similar to that of the solar wind using a two‐dimensional PIC simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Dum and Nishikawa [1994] did two‐dimensional PIC simulations of the instability in a strongly magnetized plasma, and showed weak perpendicular scattering of the beam component. Later simulations [ Yin et al , 1998; Gary et al , 2000] suggested that pitch angle widths of the beam component tend to be broader with larger frequency ratio ω e /∣Ω e ∣, where ω e and Ω e are the electron plasma and cyclotron frequencies. Lately, Gary and Saito [2007] demonstrated electron beam broadening by the e/e instability in a weakly magnetized plasma similar to that of the solar wind using a two‐dimensional PIC simulation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Dum and Nishikawa [1994] did two-dimensional PIC simulations of the instability in a strongly magnetized plasma, and showed weak perpendicular scattering of the beam component. Later simulations [Yin et al, 1998;Gary et al, 2000] suggested that pitch angle widths of the beam component tend to be broader with larger frequency ratio w e /jW e j, where w e and W e are the electron plasma and cyclotron frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Kazimura et al [24] reported that electron/electron instabilities are generated in the auroral region at ω e /Ω e < 1 by tenuous electron beam propagating in the dense plasma with a sufficiently large beam relative drift velocity. Gary et al [25] using electromagnetic linear theory and particle-in cell simulations have studied the electron/electron beam instability driven by relatively dense and fast electron beams in the plasma with ω e /Ω e = 1 (polar and auroral regimes of the terrestrial magnetosphere). They found that electron/electron beam instability can account for several properties of plasma waves observed in the auroral plasmas.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the consequences of the instability are similar: the enhanced electric field fluctuations are primarily in the beam direction and scatter the beam electrons to reduce the beam velocity and increase the parallel temperature and sometimes also the perpendicular temperature. [17][18][19] In addition, oblique whistler waves can be excited by the beam in a finite beta plasma via the Landau resonance, even when the beam is isotropic. 16,20,21 These waves occur below the electron cyclotron frequency and have both electrostatic and electromagnetic components.…”
Section: Introductionmentioning
confidence: 99%